Lectotypification of the names Festuca makutrensis and its variety, F. makutrensis var. obtecta (Poaceae) - Bednarska, Iryna O.; Mosyakin, Sergei L. (Phytotaxa, 2021)
The name Festuca makutrensis is currently accepted and considered to be applicable to a presumably hybridogenous species at present reliably known from Ukraine and Poland (records from other countries need confirmation), where it occurs mainly on humus-rich shallow soils on carbonates (rendzinas) as a component of floristically rich extrazonal meadow steppes and similar dry grasslands. The species is considered endangered in Poland. The previous attempt at type designation of F. makutrensis proved to be ineffective for nomenclatural reasons. Lectotypes are designated here for the names F. makutrensis and F. makutrensis var. obtecta, both validated by Zapałowicz simultaneously, based on specimens collected by Raciborski at the Makitra Hill (also known as Makutra Mount of the Podolia Upland; Brody District, Lviv Region, Ukraine). Since the available original herbarium sheets contain plants and plant fragments belonging to both var. makutrensis and var. obtecta (mixed collections, with plants of two varieties mounted on the same sheets), only parts of specimens/sheets from KRAM are designated as lectotypes for each name.